A case report of prenatal diagnosis of fetal alloimmune thrombocytopenia: A CARE-compliant article. Issue 24 (18th June 2021) - Fu, Jing; Yao, Ruojin; Yong, Wenjing
Abstract: Rationale: Fetal alloimmune thrombocytopenia (FAIT) is a serious life-threatening disease caused by platelet-antigen incompatibility between the mother and fetus. FAIT can lead to fetal thrombocytopenia, intracranial hemorrhage (ICH), fetal death and severe neurological disorders after birth. Noninvasive prenatal diagnosis technology has not been widely used in China, and thus few cases of FAIT can be diagnosed prenatally. In this study, we report a case of prenatal diagnosis and treatment of FAIT. Patient concerns: A 29-year-old female was admitted at 32 weeks' gestational age (GA). Fetal ultrasound at 32 weeks' GA showed a hemorrhagic focus area in the left lateral ventricle and the sign of severe fetal anemia. Hence, fetal umbilical cord puncture was ordered to identify the etiology. Diagnoses: The fetal cord blood test revealed a normal hemoglobin level but severe fetal thrombocytopenia (platelet count, 23 × 10 9 /L). Antibodies of human platelet antigens and human leukocyte antigens between mother and fetus were positive, and thus the diagnosis of FAIT was confirmed. Interventions: The patient refused intravenous immunoglobulin (IVIG) therapy owing to financial consideration. She was treated with dexamethasone acetate tablets (Xianju Company, China) 0.75 mg twice a day until delivery and cesarean section was performed at 34 weeks' GA. The newborn received postnatal anti-platelet antibody treatment. Outcomes: The platelet count of the newborn progressively decreased until the third day after birth and it increased to normal level after postnatal treatment. The neonatal cerebral ultrasound showed the area of hemorrhage was in the process of absorption. During the postnatal one-year follow-up, the neonate showed normal developmental milestones and had no abnormal signs of neurological symptoms. Lessons: For FAIT, the fetal umbilical cord puncture can be carried out by skilled fetal medical teams. Dexamethasone acetate tablets can be an alternative choice for patients from underdeveloped areas.